Factors Underlying the Graduation of Beneficiary Families of the PKH Program in Sukaluyu Village, Pangalengan District - Apriarso, Dafi; Septiarum, Anisa Fajri; Hayati, Nabila Fitri; Lutfiah, Wahdah; Sukmawati, Ellies (Pascasarjana Universitas Mataram, 2025)
The Family Hope Program (PKH) plays a strategic role in poverty alleviation through graduation, particularly independent prosperous graduation, which indicates an increase in independence and welfare of the Beneficiary Families (KPM). This research aims to identify the internal and external factors underlying independent prosperous graduation in Sukaluyu Village, Pangalengan District. By using a descriptive-qualitative approach, this study seeks to explore the factors that cause PKH KPM to want to achieve independent prosperous graduation amidst the low level of such graduation present in Sukaluyu Village. The results are expected to provide recommendations to enhance the effectiveness of the PKH program, particularly in regions with unique local characteristics. The research results indicate that there are internal and external factors consisting of effort motivation, self-awareness, family support, and business opportunities.